Change in avoidance and negative grief-related cognitions mediates treatment outcome in older adults with prolonged grief disorder. (2nd January 2022) - Lechner-Meichsner, Franziska; Mauro, Christine; Skritskaya, Natalia A.; Shear, M. Katherine
ABSTRACT: Objective: The present study investigated the role of the two theoretically derived mediators in the treatment of Prolonged Grief Disorder (PGD). Mediators were changes in avoidance and maladaptive cognitions. An additional hypothesis tested whether these candidate mediators are specific to CBT-based Complicated Grief Treatment (CGT) compared to Interpersonal Therapy (IPT). Method: We performed secondary analyses with assessment completers ( n  = 131) from a randomized-controlled trial with older adults with PGD. Patients received 16 sessions of CGT or IPT. Outcomes were treatment response and reductions in grief symptoms and grief-related related impairment. Results: Reductions in avoidance between baseline and week 16 mediated reductions in grief symptoms and grief-related impairment. Reductions in maladaptive grief-related cognitions over the same period mediated treatment response, reductions in grief symptoms and grief-related impairment. There were no significant treatment-mediator interactions. We could not establish that mediators changed before the outcomes. Conclusion: Results are consistent with theoretical models of PGD, including the CGT treatment model. Despite different therapeutic procedures, we found no significant interaction effect, but CGT produced larger effects. Future research needs to establish a timeline of change through the use of multiple measurements of mediators and outcomes. Trial registration: ClinicalTrials.gov identifier: NCT01244295.